PENGARUH MOTIVASI DAN PENGALAMAN KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN PT. SCHENEIDER ELECTRIC MANUFACTURING BATAM - Mira Yona; Luskya Sastria (EQUILIBIRIA, 2019)
This research aims to know the influence of motivation and work experiences to productivity employes of PT.Scheneider Electric Manufacturing Batam. Motivation and work experiences is one the factors that suport employee productivity.This research was conducted on a PT.Scheneider Electric Manufacturing Batam. This research aims to know the influence of motivation and work experience of employees work productivity.The number of samples specified by as much as 68 respondents. As the independents variable motivation and work experience, while the variable dependen is the employee productivity. Analyss use include test validity,reliability,test assumptions,and hypothesis testing.                 Analysis result can be seen that the variable has a positive motivation and work experience on employee performance,and the results of the analysis using the regression coefficient: (1 ) variable Motivate (X1) point tests t computing  (6. 867) T table (3,447)  and signifikansi (0. 000) of 0.005 and it menunjukan exists positive influence and signifikan for work productivity to fire an employee. (2) Job Experience variables (X2) point t computing  (6. 507) T table (4,679) and signifikansi (0. 000) of 0.005, available influence which positive and signifikan for work productivity to fire an employee. (3 ) available positive influence and signifikan is ala jointly motivates and job experiences for productivity to fire an employee with point f computing  are 147.574 F table 3.84 by signifikan assesses f computing  as big as 0.000 inferior from 0.05.Nilai signifikansi 0.000 0. 05.  Keyword : Motivation, work experience, productivity